Strategic Management and Firm Performance (International Journal of Scientific Research and Management (IJSRM), 2019)
This paper discusses the relationship between business strategies of firms and their performances. In the beginning the strategic aspects of the concept are presented, then competition and performance and their linkage to strategy is discussed. This is followed by the discussion of several empirical studies on the determinants of firm financial performance. Researches confirm that firms within the same industry differ from one another, and that there seems to be an inertia associated with these differences.